Comparative study on outcome of intralesional steroid and combination of intralesional steroid with 5-fluorouracil in keloid treatment - Augustine, Thara; Murali, Biju (International Surgery Journal, 2024)
Background: Though the definitive management of keloids are not yet established, many treatment modalities have been described which are being used alone or in combination all over the world with some promise. This study aims to assess the effect of intralesional steroids and 5-fluorouracil (5-FU) in the treatment of keloids. Methods: The study included 40 patients with keloids, out of which 20 received 6 doses of intralesional steroid and the other 20 received alternating three doses of intralesional steroid and three doses of 5-FU. The size of the keloid and the POSAS (Patient observer scar assessment scale) score were marked on the proforma and the patient was reassessed after 6 months. The decrease in volume and POSAS score was statistically analysed using paired and unpaired t tests. Results: There is a statistically significant decrease in POSAS score after intervention in both the steroid and steroid+5 FU groups. However, the decrease in POSAS score is significantly more in the group that received steroids alone. The group that received steroids had a greater decrease in volume (50% reduction) compared to the group that received the steroid-5FU combination (27% reduction). Conclusions: There is a statistically significant decrease in POSAS score after intervention in both the steroid and steroid+5 FU groups. However, the decrease in POSAS score is significantly more in the group that received steroids than the group that received steroid-5 FU combination.